Sustainable growth, input factors, and technological progress in agriculture: Evidence from 1990 to 2020 in China - Tong, Wenxia; Qin, Guangke; Xu, Yanmin; Fu, Chen (Frontiers in Environmental Science, 2023)
This paper decomposes agricultural input factors into labor, land, fertilizer, and farm machinery in 31 provinces of China from 1990 to 2020. This paper analyzes the input factor’s contribution rates to China’s agricultural growth using the stochastic frontier model. The empirical results indicate that the contribution rate of input factors in China’s agricultural growth has weakened, with decreasing contribution rate of labor, an increasing contribution rate of fertilizer and machinery, and decreasing contribution rate of the land year by year. The contribution rate of technological progress is increasing, and there is room for improvement. In addition, technological progress and input factors alternately lead to the time of policy change in China. The research also shows that the prerequisite for promoting rural supply-side reform and achieving sustained agricultural growth is ensuring a stable supply of input factors, focusing on promoting agricultural technological progress.